2020
DOI: 10.1507/endocrj.ej20-0193
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of recommendations from the international consensus on continuous glucose monitoring-derived metrics in Japanese children and adolescents with type 1 diabetes

Abstract: We assessed the significance of recommendations from the international consensus on continuous glucose monitoring (CGM)-derived metrics in Japanese children and adolescents with type 1 diabetes. Eighty-five patients (age, 13.5 ± 4.7 years) who wore the FreeStyle ® Libre for a 28-day period were enrolled in this study. Seventy-three patients were treated with multiple daily injections of insulin and 12 with insulin pump therapy without using a sensor-augmented pump or a predictive low-glucose suspend-function p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…corresponded to a TIR 70-180 of 56.1% in patients with type 1 diabetes mellitus. Furthermore, Urakami et al 34 reported that an HbA1c level of 7.0% corresponded to a TIR 70-180 of 55.1% in Japanese children and adolescents with type 1 diabetes mellitus, a finding similar to that presented in the present study. In contrast, we found that an HbA1c level of 7.0% corresponded to a TIR 70-180 of 74.2% in patients with type 2 diabetes mellitus, which differed from the values of those with type 1 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…corresponded to a TIR 70-180 of 56.1% in patients with type 1 diabetes mellitus. Furthermore, Urakami et al 34 reported that an HbA1c level of 7.0% corresponded to a TIR 70-180 of 55.1% in Japanese children and adolescents with type 1 diabetes mellitus, a finding similar to that presented in the present study. In contrast, we found that an HbA1c level of 7.0% corresponded to a TIR 70-180 of 74.2% in patients with type 2 diabetes mellitus, which differed from the values of those with type 1 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 91%
“…The present study found that an HbA1c level of 7.0% corresponded to a TIR 70–180 of 56.1% in patients with type 1 diabetes mellitus. Furthermore, Urakami et al 34 . reported that an HbA1c level of 7.0% corresponded to a TIR 70–180 of 55.1% in Japanese children and adolescents with type 1 diabetes mellitus, a finding similar to that presented in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that low TAR had a signi cant association with TBR ≥ 1%. While few studies have investigated the relationship between TAR and TBR in patients with type 2 diabetes, one study conducted CGM in 85 children and adolescents with type 1 diabetes and showed a weak inverse correlation between TAR and TBR [22]. This nding is compatible with our results.…”
Section: Discussionsupporting
confidence: 92%
“…What else do we need to improve? Certainly a more general access to the CGM technology for all individuals with T1D, in the less affluent environments; wider availability of CGM for individuals with T2D; more individualized approaches in CGM implementation for every person with diabetes (43); and firm establishment of CGM-derived metrics like TIR/TBR as primary outcomes in clinical trials. Engaging the regulatory bodies would certainly help.…”
Section: Discussionmentioning
confidence: 99%